Львівські періодичні видання у фондах НБУВ: історія формування та тематичний склад - Гуржій, І. (Краєзнавство, 2023)
Актуальність теми. На основі архівних джерел і друкованих матеріалів Національної бібліотеки України імені В. І Вернадського (НБУВ) висвітлено історію формування львівських періодичних видань другої половини XIX - початку ХХ ст. і їхнє укомплектування у відділі бібліотечних зібрань та історичних колекцій. Визначено та проаналізовано тематику та етапи накопичення опублікованих зібрань. Також наводиться огляд вміщених на їхніх шпальтах студій, які мали особливу актуальність і оприлюднювались у регіональних виданнях. Оціночні характеристики зроблені в даному дослідженні мають вагоме значення для вивчення історії розвитку української культури: освіти, мови, права та друкарської справи, а також поширення національних ідей, сформульованих львівськими дописувачами. Об’єктом дослідження є інтегрований фонд документів НБУВ як сукупність всіх різноманітних книжкових, журнальних, газетних, а також і недрукованих джерел інформації, що запроваджуються бібліотекою суспільного наукового та культурного обігу. Предмет дослідження становлять формування та перспективи розвитку фонду періодичних видань, що завдяки своїй історико-культурній, освітній і науково-інформаційній цінності являється яскравим показником функціонування бібліотеки, зокрема НБУВ. Хронологічні межі дослідження - саме характерний період становлення регіональної періодики охоплюють друг. пол. XIX - поч. ХХ ст. Методологія роботи - це комплексний підхід у процесі дослідження предмету, що ґрунтується на принципах історизму та наукової об’єктивності. Також використано історико-порівняльний і системний підходи та книгознавчий аналіз. Наукова новизна полягає у представлені західноукраїнської преси як складової відділу періодичних видань НБУВ, де вперше проведено змістовний книгознавчий аналіз, проаналізовано розподіл періодичних видань за тематикою. Зроблено спробу простеження шляху, яким примірники львівських видань потрапили до фонду бібліотеки. Джерельною базою дослідження є архівні матеріали з фондів інституту рукопису НБУВ, архіву НБУВ, опублікованих праць про діяльність НБУВ, наукові праці з історії вивчення преси, книгознавства, бібліотекознавства, документознавства. Висновки. Виявлення львівських періодичних видань, раніше малодосліджені у бібліографії, свідчить про необхідність продовження дослідницької роботи з бібліотечними фондами та колекціями української книги. Наукова періодика зазначеного періоду в дослідженні відіграє важливу роль у становленні й розвитку бібліотечної справи, оскільки на своїх сторінках відображає не тільки актуальні проблеми бібліотекознавства, а й також висвітлює події суспільно-політичного та культурного життя, які безпосередньо мали вплив на розвиток науки в цілому. Actuality of theme. On the basis of archival sources and printed materials of the NBUV, the history of the formation of Lviv periodicals of the second half of the 19th – beginning of the 20th centuries is highlighted. The topics and stages of accumulation of book collections are defined and analyzed. Also, an overview of materials that were relevant in the 20th century and published in periodicals is provided. The evaluation characteristics made in this study are of great importance for the study of the history of the development of Ukrainian culture: education, language, law, and printing. The object of the research is the integrated fund of documents of the NBUV as a collection of all various book, magazine, newspaper, as well as non-printed sources of information introduced by the public scientific and cultural circulation library. The subject of the study is the formation and prospects of the development of the fund of periodicals, which, thanks to its historical, cultural, educational, scientific and informational value, is a vivid indicator of the functioning of the library, in particular the NBUV. Chronological boundaries of the study – Cover friend. gender XIX – beginning 20th century The methodology of the work is a complex approach in the process of researching the subject, based on the principles of historicism and scientific objectivity. A historical-comparative, systematic approach and bibliographic analysis were also used. The Scientific novelty lies in the presentation of the Western Ukrainian press as a component of the NBUV periodicals department, where for the first time a meaningful bibliographic analysis was conducted, and the distribution of periodicals by topic was analyzed. An attempt was made to trace the path by which copies of Lviv editions got to the library fund. The source base of the research is archival materials from the funds of the Institute of Manuscripts of the NBUU, the archives of the NBUU, published works on the activities of the NBUU, scientific works on the history of the study of the press, bibliography, library science, and document studies. Conclusion. So, in this study, pre-revolutionary Lviv periodicals are comprehensively characterized for the first time, and special attention is paid to those of them stored in the department of library collections and historical collections of the V. I. Vernadskyi National Library. The thematic direction of Lviv periodicals is determined and the history of the formation of periodicals from the middle of the 19th to the beginning of the 20th century is traced. Materials published in Lviv periodicals and relevant to the contemporary reader were also analyzed in detail. Surviving copies of Lviv editions went through a difficult path, «traveling» for a long time in various archival repositories of the USSR, before getting into the collection of pre-revolutionary periodicals, which is now kept in the NBUV fund. In the research, it is no less important to provide information about unique historical figures who were undoubtedly associated with publishing activities not only in Lviv, but also in other Western European cities. The information presented in this essay still has not lost its scientific significance and continues to attract the attention of scientists in search of novelty and interesting material for further work.